Is Cladophora fracta an efficient tool of accumulating critical raw materials from wastewater and there a potential health risk of use of algae as organic fertilizer? - Topal, E. Isil Arslan; Obek, Erdal; Topal, Murat (Taylor & Francis Ltd, 2024)
In this study investigation of accumulations of critical raw materials (cobalt (Co), antimony (Sb), vanadium (V), lanthanum (La) and tungsten (W)) from wastewater by using C. fracta were aimed. Besides, assessment of the potential health risks in terms of the use of organic fertilizer obtained from the macroalga to be harvested from the treatment were also aimed. Highest Co, Sb, V, La and W accumulations by algae in reactor were 125 +/- 6.2%, 201.25 +/- 10%, 318.18 +/- 15%, 357.97 +/- 18%, and 500 +/- 25%, respectively. When compared with control, Co, Sb, V, La and W in algae increased 2.25, 3.01, 4.18, 4.58, and 6 times, respectively. The algae was very high bioaccumulative for Co and La. Highest MPI was calculated as 3.94. Non-carcinogenic risk of CRMs according to different exposure types (ingestion, inhalation, and dermal) were calculated for man, woman and child. There is not any non-carcinogenic risk from the investigated exposure ways of algae as organic fertilizer.
Keywords: Cancer; critical raw materials; health; risk